Analysis of Technical Guidance Implementation: Evaluation of Voting and Vote Counting by KPPS in the 2024 Election in North Petukangan - Jatmiko Putri, Khansa Khairun Nisa; Khaila, Ananda Putri; Firmansyah, Fadly; Nainggolan, Dina Thalentaria; Azmy, Ana Sabhana (Universitas Muhammadiyah Makassar, 2024)
Elections are a characteristic of a democratic country, held once every 5 years in Indonesia. The holding of democratic elections can’t be separated from the democratic implementation process. Since 2015, elections have been held simultaneously. The 2024 elections will include legislative and presidential votes. In the 2024 elections, several problems have arisen due to the limited number and experience of PPS members, the